Poezja w klinczu (z)rozumienia - Kozicka, Dorota (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
The article presents polemic discussions of poetry referred to as hermetic or obscure; the discussion has been ongoing for the past twenty five years. In more general terms, the dispute is over the issue of the incomprehensible nature of poetry. The most heated stages of the discussion reveal the basic and repeated arguments put forward by both parties, as well as  the differences in the perspectives and points of reference, indicating the changes which occurred in literature in the meantime.